Digital collection development strategy on e-Pusda Probolinggokab application - Qonita, Tutut Nailul; Syahri, Moch (Berkala Ilmu Perpustakaan dan Informasi, 2025)
Introduction. This research aims to describe the process of developing digital collections on e-Pusda Probolinggokab and find out the obstacles faced with a focus on analysing strategies applied in order to achieve operational efficiency and reduce obstacles that will occur. E-Pusda Probolinggokab is a digital library to provide better services and attract user attention. Digital collection development is an indicator to be researched considering people low reading interest. This is evidenced by the acquisition of a C accreditation predicate from the self-assessment results. Data Collection Methods. The method used was descriptive qualitative. Data collection techniques used interviews, observation, and documentation. Data Analysis. We analysed that data using the stages of digital collection development developed by Sanchez and Lourdes. Results and Discussion. The collection management on the platform has been conducted by selecting and purchasing from providers, evaluating collection information based on user feedback, managing collection structures through provider classification, building digital collection development based on collection development policies, and maintaining digital collections by monitoring applications. No significant obstacles were found, although the library has not felt optimal in socializing the e-Pusda Probolinggokab application. Conclusion. The digital collection development strategy is implemented efficiently, displaying user-friendly application, however, the existence of e-Pusda Probolinggokab is necessary to support to increase user numbers.